LEGALITAS MEREK DAGANG DAN KEMITRAAN USAHA PADA UNIT PERDAGANGAN BUMDES NIAGARA - Trisa Nur Kania; Latifah Adnani (Universitas Ahmad Dahlan, 2019)
Law Number 20 of 2016 in Indonesia regulates brands and geographical indications (hereinafter referred to as Trademark Law). For businesses, making an effort to legalize the brand of the products/services they sell is important, even though in reality, many business actors do not understand this. This study aims to find out, analyze and provide insight into knowledge and understanding of businesses about the importance of a product being given a trademark and legally legalized through trademark registration to the state. Other than that, the other purpose of this research is to provide business partners with an understanding of business partnerships. The research method uses case studies with the consideration that the focus of the research is on contemporary (present) phenomena in the context of real life. The results showed that the business actors did not understand the rules relating to trademark design and procedures for trademark registration and did not understand the business contract with business partners. Therefore, in order to help solve the problems faced by business actors, the community service activities are carried out in stages, namely: provide counseling on regulations and laws related to trademark and assistance in the procedure for trademark registration, as well as assistance in making business contracts with business partners.